Barriers towards widespread adoption of V2G technology in smart grid environment: From laboratories to commercialization - Adnan, N. (Springer International Publishing, 2018)
A new era of transportation has experienced electrification and undergoes notable changes in the last few decades. The concern about environmental friendly technology carries almost a huge expansion prospect to electric vehicles (EVs). Whereas plug-in hybrid electric vehicles (PHEVs) are recognized as a feasible term in the line of vehicular technology in the smart electric grid to lessen the dependency on fossil fuels and greenhouse gas (GHG) emissions related to conventional vehicles (CVs). The development of vehicle-to-grid (V2G) strategies establishes winâwin situations for the PHEV participation without additional infrastructure cost, reduction of generation, operational and PHEV user cost, reduction of environmental pollution. Together with the expansion of the smart grid technologies, the V2G power allocation problems need to be addressed. More originally, this chapter measures substantial, though often overlooked, social barriers to the wider use of PHEVs (a likely precursor to V2G) and implementation of a V2G transition. This chapter has given an idea that the only important barriers facing the greater use of PHEVs and V2G systems are technical. Instead, it provides a broader assessment situating such âtechnicalâ barriers alongside more subtle impediments relating to social and cultural values, business practices, and political interests. Thus, this research study recognizes probable socio-technical obstacles towards widespread adoption of V2G in smart grid and governs that if sustainability problems affect consumer decision to adopt V2G to charge their PHEVs. The current study delivers valuable understanding about the perception among technology fanatics associated with knowledge expansion and improved fortified to sort out the numerous alterations among V2G and PHEVs. Finally, the outcomes of this chapter can guide policy makers to implement V2G technology successfully. Moreover, the chapter illuminates the policy implication of such barriers, which emphasizes what policy makers need to achieve towards V2G technology adoption in smart grid environment while integrating electric vehicles engineering with consumer preference. Â© Springer International Publishing AG, part of Springer Nature 2018.